Early visibility of cellular aggregates and changes in central corneal thickness as predictors of successful corneal endothelial cell injection therapy - Wong, Evan N. (2023)
(1) Background: Cell injection therapy is an emerging treatment for bullous keratopathy (BK). Anterior segment optical coherence tomography (AS-OCT) imaging allows the high-resolution assessment of the anterior chamber. Our study aimed to investigate the predictive value of the visibility of cellular aggregates for corneal deturgescence in an animal model of bullous keratopathy. (2) Methods: Cell injections of corneal endothelial cells were performed in 45 eyes in a rabbit model of BK. AS-OCT imaging and central corneal thickness (CCT) measurement were performed at baseline and on day 1, day 4, day 7 and day 14 following cell injection. A logistic regression was modelled to predict successful corneal deturgescence and its failure with cell aggregate visibility and CCT. Receiver-operating characteristic (ROC) curves were plotted, and areas under the curve (AUC) calculated for each time point in these models. (3) Results: Cellular aggregates were identified on days 1, 4, 7 and 14 in 86.7%, 39.5%, 20.0% and 4.4% of eyes, respectively. The positive predictive value of cellular aggregate visibility for successful corneal deturgescence was 71.8%, 64.7%, 66.7% and 100.0% at each time point, respectively. Using logistic regression modelling, the visibility of cellular aggregates on day 1 appeared to increase the likelihood of successful corneal deturgescence, but this did not reach statistical significance. An increase in pachymetry, however, resulted in a small but statistically significant decreased likelihood of success, with an odds ratio of 0.996 for days 1 (95% CI 0.993-1.000), 2 (95% CI 0.993-0.999) and 14 (95% CI 0.994-0.998) and an odds ratio of 0.994 (95% CI 0.991-0.998) for day 7. The ROC curves were plotted, and the AUC values were 0.72 (95% CI 0.55-0.89), 0.80 (95% CI 0. 62-0.98), 0.86 (95% CI 0.71-1.00) and 0.90 (95% CI 0.80-0.99) for days 1, 4, 7 and 14, respectively. (4) Conclusions: Logistic regression modelling of cell aggregate visibility and CCT was predictive of successful corneal endothelial cell injection therapy.